Decomposition of aged sedimentary organic matter in a deep temperate lake under warming conditions: An experimental approach - Wataru Nakamura; Yasuhiko T. Yamaguchi; Shish Muhammad Soyaib; Sho Ogasawara; Eiso Inoue; Koichi Shimotori; Yosuke Miyairi; Yusuke Yokoyama (Water Research, 2026)

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Monitoring the immune landscape against rabies in domestic dogs, Japan - Yuri Amemiya; Satoshi Inoue; Ken Maeda; Akira Nishizono; Yusuke Inoue; Naoto Ito; Hiroshi Nishiura (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Opposite latitudinal biodiversity gradient in the open ocean generated by transition zones: Insights from fish distribution in the Northwest Pacific - Yuan Lin; Zeshu Yu; Sk Istiaque Ahmed; Xueding Wang; Tomihiko Higuchi; Itsuka Yabe; Marty Kwok-Shing Wong; Sachihiko Itoh; Eisuke Tsutsumi; Hiroaki Saito; Kosei Komatsu; Atsushi Tsuda; et al. (Progress in Oceanography, 2026)

In-phase variation along the Nankai trough in the ocean bottom temperature records of DONET - Tomohiro Inoue; Yusuke Yokota; Tatsuya Kubota (Journal of Oceanography, 2026)
Ocean bottom temperature is affected by waves propagating along the seafloor. Understanding fluctuations in ocean bottom temperature caused by such wave phenomena can enhance the accuracy of geophysical observations. If seafloor seismic observation networks such as the Dense Ocean floor Network system for Earthquakes and Tsunamis (DONET), which was installed for earthquake disaster prevention in the Nankai Trough region, can detect ocean waves generated along the continental slope, they may serve broader multidisciplinary research objectives across various ocean bottom seismic networks. Here, we investigated the spatiotemporal characteristics of ocean bottom temperature data recorded by DONET and identified in-phase wave patterns. Our findings reveal that temperature correlations are more strongly dependent on relative water depths than on the horizontal distances between observation sites. Such in-phase variations observed in DONET thermometers suggest that seafloor seismic networks can indeed detect and assess oceanographic phenomena such as wave propagation. Furthermore, we discuss the implications of such wave activity on the accuracy of distributed acoustic sensing (DAS) data used in geophysical studies, highlighting potential applications of DAS in oceanography and its relevance to crustal deformation observation.

Fish species detection by environmental DNA metabarcoding by three surface sampling methods - Sk Istiaque Ahmed; Zeshu Yu; Tomihiko Higuchi; Jun Inoue; Marty Kwok-Shing Wong; Susumu Yoshizawa; Sachihiko Itoh; Kosei Komatsu; Yusuke Kawaguchi; Eisuke Tsutsumi; Yuan Lin; Susumu Hyodo; et al. (Regional Studies in Marine Science, 2025)

Angiogenic Ability of Extracellular Vesicles Derived from Angio-miRNA-Modified Mesenchymal Stromal Cells - Yoshiki Wada; Toshifumi Kudo; Anri Koyanagi; Tomomi Kusakabe; Ayako Inoue; Yusuke Yoshioka; Takahiro Ochiya; Shoji Fukuda (Tissue Engineering and Regenerative Medicine, 2025)
Background: Regenerative therapy using extracellular vesicles (EVs) is a promising approach for the supportive treatment of chronic limb-threatening ischaemia. Herein, we examined the angiogenic potential of EVs derived from genetically modified mesenchymal stromal cells (MSCs), focusing on the angio-micro RNAs (miRNAs) in EVs. Methods: Bone marrow-derived MSCs (BM-MSCs) were transfected with lentiviral vectors containing specific angio-miRNAs (miRNA-126, -135b, or -210), and miRNA overexpression was confirmed using quantitative polymerase chain reaction (qPCR). EVs were isolated from the BM-MSC culture medium and characterised using fluorometry, nanoparticle tracking analysis, and ExoScreen assays. In vitro, human umbilical vein endothelial cells (HUVECs) were used to evaluate the angiogenic potential of the EVs. In vivo , EVs were injected into the ischaemic hindlimb muscles of mice, and limb ischaemia severity, blood perfusion, and histological analysis of muscle tissue were performed. Results: qPCR analysis confirmed the overexpression of angio-miRNAs in MSCs transfected with lentiviral vectors. Isolated EVs expressed CD63 and had consistent protein-to-particle ratios. Tube formation was significantly enhanced when HUVECs were cultured with EV126, EV135b, or their combination (EV126 + EV135b) ( p < 0.05), compared to BM-MSC co-culture. In vivo , only the double and triple EV groups significantly improved limb perfusion compared to the EVcontrol ( p < 0.05); single EVs showed no significant difference. Histological analysis showed increased capillary density in ischaemic muscles following injection of combined EVs. Conclusion: EVs derived from genetically modified MSCs promoted angiogenesis both in vitro and in vivo , with a combination of modified EVs demonstrating significantly superior therapeutic effects than single or native EVs.

Oligomeric secoiridoid glycosides with hepatoprotective activity from the flowers of Jasminum sambac (L.) Aiton - Naoki Inoue; Yusuke Sakamoto; Yoshiaki Manse; Kiyofumi Ninomiya; Toshio Morikawa (Phytochemistry, 2025)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Enhanced design of pCMViR-TSC plasmid vector for sustainably high cargo gene expression in mammalian cells - Masakiyo Sakaguchi; Rie Kinoshita; Nahoko Tomonobu; Yoshihiko Sakaguchi; Junichiro Futami; Akira Yamauchi; Hitoshi Murata; Ken-ichi Yamamoto; Tetta Takahashi; Yuma Gohara; Toshiki Ochi; Fan Jiang; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)
The first-generation pCMViR-TSC, implemented through the promoter sandwich rule, yields 10- to 100-fold higher gene expression than the standard plasmid used with the CMV (cytomegalovirus) or CAG promoter. However, the vector’s shortcomings limit its utility to transient expression only, as it is not suitable for establishing stable transformants in mammalian cells. To overcome this weakness, we here introduce the improved plasmid vector pSAKA-4B, derived from pCMViR-TSC as a second-generation chromosome-insertable vector. This vector facilitates the linear entry of the expression unit into the TTAA site of DNA universally with transposase assistance. The vector is helpful for the indefinite expression of our target gene. The new vector system is proven here to be efficient in establishing stable transformants with a high likelihood of positive clones that exhibit significantly elevated expression levels of the delivered foreign gene. This system, alongside the first-generation vector, is therefore instrumental for diverse basic research endeavors concerning genes, proteins, cells, and animals, and potentially for clinical applications such as gene therapy.

Hepatocyte nuclear factor 4α is a critical factor for the production of complement components in the liver - Carlos Ichiro Kasano-Camones; Satomi Yokota; Maiko Ohashi; Noriaki Sakamoto; Daichi Ito; Yoshifumi Saito; Ryo Uchida; Kazumi Ninomiya; Yusuke Inoue (In Vitro Cellular & Developmental Biology - Animal, 2024)

Efficacy of a DNA vaccine encoding the E2 glycoprotein of bovine viral diarrhea virus 1 fused to mouse lysosome-associated membrane protein 1 - Yusuke Sakai; Shinji Yamada; Maho Inoue; Toshinori Shiga; Kotomi Konagayoshi; Kei Kasai; Atsushi Kimura; Kenji Murakami (Veterinary Microbiology, 2024)

Effects of different exercise modes and intensities on cognitive performance, adult hippocampal neurogenesis, and synaptic plasticity in mice - Hanlin Jiang; Yusuke Kimura; Shota Inoue; Changxin Li; Junpei Hatakeyama; Masahiro Wakayama; Daisuke Takamura; Hideki Moriyama (Experimental Brain Research, 2024)

New geocell utilisation as a pipe uplifting countermeasure and its validation using model experiments - Taishi Nagatani; Yutaka Sawada; Yusuke Inoue; Shuji Ito; Hoe I. Ling; Toshinori Kawabata (Geotextiles and Geomembranes, 2024)

Modulation of plant immunity and biotic interactions under phosphate deficiency - Kanako Inoue; Natsuki Tsuchida; Yusuke Saijo (Journal of Plant Research, 2024)

Description of a new species, Pseudodiscocotyla mikiae n. sp. (Monogenea: Discocotylidae) parasitic on gills of Pristipomoides filamentosus from off Okinawa-jima island in Japan, with redescription of Pseudodiscocotyla opakapaka - Yusuke Kamio; Aina Inoue; Masato Nitta (Systematic Parasitology, 2023)

Correlation between cytochrome P450 1A (cyp1a) mRNA expression and ambient phenanthrene and pyrene concentration in Javanese Medaka Oryzias javanicus - Suhaila Rusni; Mieko Sassa; Yusuke Takehana; Masato Kinoshita; Koji Inoue (Fisheries Science, 2020)

New Cerebello-Cortical Pathway Involved in Higher-Order Oculomotor Control - Xiaofeng Lu; Ken-ichi Inoue; Shogo Ohmae; Yusuke Uchida (The Cerebellum, 2020)

Changes in phytoplankton community structure during wind-induced fall bloom on the central Chukchi shelf - Amane Fujiwara; Shigeto Nishino; Kohei Matsuno; Jonaotaro Onodera; Yusuke Kawaguchi; Toru Hirawake; Koji Suzuki; Jun Inoue; Takashi Kikuchi (Polar Biology, 2018)

Reinereins A and B, new onocerane triterpenoids from Reinwardtiodendron cinereum - Alfarius Eko Nugroho; Daisuke Inoue; Chin Piow Wong; Yusuke Hirasawa; Toshio Kaneda; Osamu Shirota; A. Hamid A. Hadi; Hiroshi Morita (Journal of Natural Medicines, 2018)

Antithrombotic Protein Filter Composed of Hybrid Tissue-Fabric Material has a Long Lifetime - Yusuke Inoue; Tomoyuki Yokota; Tsuyoshi Sekitani; Akiko Kaneko; Taeseong Woo; Shingo Kobayashi; Tomokazu Shibuya; Masaru Tanaka; Hiroyuki Kosukegawa; Itsuro Saito; Takashi Isoyama; Yusuke Abe; et al. (Annals of Biomedical Engineering, 2017)

A mouse model reveals that Mfsd2a is critical for unfolded protein response upon exposure to tunicamycin - Hiroshi Moritake; Megumi Obara; Yusuke Saito; Ayako Kashimada; Masatoshi Takagi; Megumi Funakoshi-Tago; Tomofusa Fukuyama; Mikio Yoshioka; Akira Inoue; Hiroyuki Komatsu; Hideki Nishitoh; Hiroaki Kataoka; et al. (Human Cell, 2017)

Coupled Response of Bacterial Production to a Wind-Induced Fall Phytoplankton Bloom and Sediment Resuspension in the Chukchi Sea Shelf, Western Arctic Ocean - Mario Uchimiya; Chiaki Motegi; Shigeto Nishino; Yusuke Kawaguchi; Jun Inoue; Hiroshi Ogawa; Toshi Nagata (Frontiers in Marine Science, 2016)

MCAM, as a novel receptor for S100A8/A9, mediates progression of malignant melanoma through prominent activation of NF-κB and ROS formation upon ligand binding - I. Made Winarsa Ruma; Endy Widya Putranto; Eisaku Kondo; Hitoshi Murata; Masami Watanabe; Peng Huang; Rie Kinoshita; Junichiro Futami; Yusuke Inoue; Akira Yamauchi; I. Wayan Sumardika; Chen Youyi; et al. (Clinical & Experimental Metastasis, 2016)

Spectrum of mutations and genotype–phenotype analysis in Noonan syndrome patients with RIT1 mutations - Masako Yaoita; Tetsuya Niihori; Seiji Mizuno; Nobuhiko Okamoto; Shion Hayashi; Atsushi Watanabe; Masato Yokozawa; Hiroshi Suzumura; Akihiko Nakahara; Yusuke Nakano; Tatsunori Hokosaki; Ayumi Ohmori; et al. (Human Genetics, 2016)

Genetic similarity of the Hainan medaka populations collected from hyper- and hypo-osmotic environments in northern Vietnam - Hideki Hayakawa; Quang Dung Le; Masato Kinoshita; Yusuke Takehana; Kei Sakuma; Hirohiko Takeshima; Shigeaki Kojima; Kiyoshi Naruse; Koji Inoue (Ocean Science Journal, 2015)

Vertical heat transfer based on direct microstructure measurements in the ice-free Pacific-side Arctic Ocean: the role and impact of the Pacific water intrusion - Yusuke Kawaguchi; Takashi Kikuchi; Ryuichiro Inoue (Journal of Oceanography, 2014)

Fibroblast growth factor 23 enhances renal klotho abundance - Tsuneo Takenaka; Yusuke Watanabe; Tsutomu Inoue; Takashi Miyazaki; Hiromichi Suzuki (Pflügers Archiv - European Journal of Physiology, 2013)

Compensatory Recovery of Blood Glucose Levels in KKAy Mice Fed a High-Fat Diet: Insulin-Sparing Effects of PACAP Overexpression in β Cells - Yusuke Sakurai; Hiroaki Inoue; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Atsuko Hayata-Takano; Akemichi Baba; Hitoshi Hashimoto (Journal of Molecular Neuroscience, 2012)

Input, retention, and invertebrate colonization of allochthonous litter in streams bordered by deciduous broadleaved forest, a conifer plantation, and a clear-cut site in southwestern Japan - Mikio Inoue; Sei-ichi Shinotou; Yusuke Maruo; Yo Miyake (Limnology, 2012)

Quantitative Effect of Reducing Body Thickness on Visualizing Murine Deep Abdominal Lymph Nodes by In Vivo Fluorescence Reflectance Imaging - Yusuke Inoue; Makoto Watanabe; Shigeru Kiryu; Kuni Ohtomo (Journal of Fluorescence, 2011)

Cerulein-Induced Acute Pancreatitis in PACAP Knockout Mice - Yusuke Sakurai; Norihito Shintani; Akihiro Arimori; Ken-ichi Hamagami; Naoko Higuchi; Hiroaki Inoue; Kazuya Ikeda; Atsuko Hayata; Hitoshi Hashimoto; Akemichi Baba (Journal of Molecular Neuroscience, 2011)

Seasonal variation of 228Ra/226Ra ratio in surface water from the East China Sea and the Tsushima Strait - Mutsuo Inoue; Yusuke Nakano; Yoko Kiyomoto; Hisaki Kofuji; Yasunori Hamajima; Masayoshi Yamamoto (Journal of Oceanography, 2010)

Fluorescence Lymph Node Mapping in Living Mice Using Quantum Dots and a Compression Technique - Yusuke Inoue; Shigeru Kiryu; Makoto Watanabe; Naoki Oyaizu; Kuni Ohtomo (Journal of Fluorescence, 2010)

Spermidine levels are implicated in heavy metal tolerance in a spermidine synthase overexpressing transgenic European pear by exerting antioxidant activities - Xiao-Peng Wen; Yusuke Ban; Hiromichi Inoue; Narumi Matsuda; Takaya Moriguchi (Transgenic Research, 2010)

Resolution of secondary alcohols via Carica papaya lipase-catalyzed enantioselective acylation - Toshifumi Miyazawa; Mika Houhashi; Yusuke Inoue; Takashi Murashima; Takashi Yamada (Biotechnology Letters, 2008)

Simple coprecipitation method combined with low-background γ-spectrometry: Determination of 7Be, 137Cs, 210Pb, and radium and thorium isotopes in small-volume coastal water samples - Yusuke Nakano; Mutsuo Inoue; Kazuhisa Komura (Journal of Oceanography, 2008)

Role of hepatocyte nuclear factor 4α in control of blood coagulation factor gene expression - Yusuke Inoue; L. Luanne Peters; Sun Hee Yim; Junko Inoue; Frank J. Gonzalez (Journal of Molecular Medicine, 2006)

Role of hepatocyte nuclear factor 4α in control of blood coagulation factor gene expression - Yusuke Inoue; Luanne L. Peters; Sun Hee Yim; Junko Inoue; Frank J. Gonzalez (Journal of Molecular Medicine, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Food habits of fishes in the surf zone of a sandy beach at Sanrimatsubara, Fukuoka Prefecture, Japan - Takashi Inoue; Yusuke Suda; Mitsuhiko Sano (Ichthyological Research, 2005)

Establishment of a human hepatoma cell line, HLE/2E1, suitable for detection of P450 2E1-related cytotoxicity - Isao Nozaki; Toshiya Tsuji; Masakiyo Sakaguchi; Yusuke Inoue; Ryuji Hirai; Akio Andou; Masahiro Miyazaki; Nobuyoshi Shimizu; Masayoshi Namba (In Vitro Cellular & Developmental Biology - Animal, 2000)

ESTABLISHMENT OF A HUMAN HEPATOMA CELL LINE, HLE/2E1, SUITABLE FOR DETECTION OF P450 2E1-RELATED CYTOTOXICITY - ISAO NOZAKI; TOSHIYA TSUJI; MASAKIYO SAKAGUCHI; YUSUKE INOUE; RYUJI HIRAI; AKIO ANDOU; MASAHIRO MIYAZAKI; NOBUYOSHI SHIMIZU; MASAYOSHI NAMBA (In Vitro Cellular & Developmental Biology - Animal, 2000)